Mouth Melting Tablets an Overview - Archana Kumari (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Mouth Melting tablets/ fast disintegrating tablets (FDTs) are receiving increased demand from last few decades and the field has become a very fast growing area in the pharmaceutical industry. After administration into the mouth, these tablets dissolve or disintegrate in the mouth without any additional water for easy administration of active pharmaceutical ingredients. These tablets readily dissolve or disintegrate in the saliva generally within seconds. Fast dissolving tablets/ mouth melting tablets have been formulated for pediatric, geriatric, bedridden patients and for active patients who are busy and traveling and may not have access to water. These tablet formulations provide a very good opportunity for product line extension in the many elderly persons will have difficulties in taking conventional oral dosage forms (viz., solutions, suspensions, tablets, and capsules) because of hand tremors and dysphasia.